2012
DOI: 10.1111/j.1745-4514.2012.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Trypsin-Like Protease from Flatfish (Paralichthys olivaceus) Intestine

Abstract: A trypsin-like protease was purified from the intestine of flatfish (Paralichthys olivaceus) by gel filtration and anion-exchange chromatography. The molecular weight was estimated to be 29.6 kDa by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Flatfish protease had maximal activity at 70C and pH 7.5 using N-a-benzoyl-dl-arginine-r-nitroanilide as substrate. It was stable to heat treatment up to 50C and to pH ranges between 7.0 and 10.0. It was activated by calcium ion and completely inhibited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…However, an increase up to 75 °C resulted in decreased activity (Figure 7). These are similarly to previous studies on Paralichthys olivaceus (Kim and Jeong, 2013), Sardenella longiceps (Khandagale et al, 2017), and Acanthopagrus latus (Namjou et al, 2019). However, they are different from Helicoverpa armigera (Grover et al, 2018) and O. niloticus (Prihanto et al, 2019) which have optimal alkaline protease activity at 50 °C and 35 °C and decreased at 60 °C.…”
Section: Pepsin and Trypsin-like Activitiessupporting
confidence: 91%
“…However, an increase up to 75 °C resulted in decreased activity (Figure 7). These are similarly to previous studies on Paralichthys olivaceus (Kim and Jeong, 2013), Sardenella longiceps (Khandagale et al, 2017), and Acanthopagrus latus (Namjou et al, 2019). However, they are different from Helicoverpa armigera (Grover et al, 2018) and O. niloticus (Prihanto et al, 2019) which have optimal alkaline protease activity at 50 °C and 35 °C and decreased at 60 °C.…”
Section: Pepsin and Trypsin-like Activitiessupporting
confidence: 91%
“…In this study, trypsin activity presented optimal activity at pH 9.5. For Thunnus orientalist, the highest trypsin activity was observed at pH 8.0, while the same was observed for Paralichthys olivaceus at pH 7.5 (Parra et al, 2007;Kim and Jeong, 2013).…”
Section: Effect Of Phmentioning
confidence: 52%
“…Peptidase inhibition patterns observed here were not similar to those observed in other species of fish, and neither were the degrees of inhibition. Kim and Jeong (2013) observed complete inhibition for purified trypsin using PMSF, benzamidine and TLCK in olive flounder intestine. Klomklao et al (2007Klomklao et al ( , 2010) also found complete inhibition in both TLCK and for TPCK for Katsuwonus pelamis and Cololabis saira.…”
Section: Effect Of Inhibitorsmentioning
confidence: 99%
“…The specific activity of the enzyme was 0.256 U/mg. The unit (U) indicates the quantity of the enzyme that catalyzes the reaction of 1 mol of substrate per minute at optimum conditions [19]. Table 1 shows that the activity of the trypsin isolated from yellowfin tuna is almost the same as that isolated from the intestines of little tuna (0.290 U/mg) [20].…”
Section: Trypsin Activity Crude Extract and Trypsin Powder Without Mi...mentioning
confidence: 99%